The genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae: Syllinae) from Australia (Fourth part) - Martín, Guillermo San; Lucas, Yolanda; Hutchings, Pat (Zootaxa, 2024)
Syllis Savigny in Lamarck, 1818, the type genus of Syllidae, is the largest and most diverse within the family. This genus presents many taxonomic, biogeographic, and phylogenetic problems due mainly to the lack of molecular data and morphological synapomorphies for many of the species, but also due to poor or inadequate descriptions. In order to improve our understanding of the genus, we have undertaken a morphological revision of Australian species, based on type material and material collected over years by the Australian Museum. This is the fourth paper dealing with this genus. Nine species are herein described, of which five are new records for Australia: Syllis ergeni Çinar, 2005; S. patersoni Soto, San Martín & Lucas, 2020; S. valida Grube, 1857; S. violacea Grube, 1870; and S. ypsiloides Aguado, San Martín & ten Hove, 2008. Three species already known from Australia are redescribed: S. heronislandensis (Hartmann-Schröder, 1991) n. comb.; S. parturiens Haswell, 1920; and S. cf. schmardiana Haswell, 1886. Syllis gantheaumensis (Hartmann-Schröder, 1979) n. comb. is raised to species level, since it was originally described as a subspecies of Typosyllis filidentata Hartmann-Schröder, 1962. We include an addendum with a list of species already treated in the previous papers on this genus, as well as some new synonymies after revision of types: Typosyllis (Typosyllis) gerhardi Hartmann-Schröder, 1980 and T. (T.) guildertonensis Hartmann-Schröder, 1979, as synonymous of Syllis busseltonensis (Hartmann-Schröder, 1982); T. (T.) raygeorgei Hartmann-Schröder, 1979 as synonymous of S. hyalina Grube, 1863; T. (T.) rockinghamensis Hartmann-Schröder, 1983 and T. (T.) pseudopapillata Hartmann-Schröder, 1991 as synonymous of S. pharobroomensis (Hartmann-Schröder, 1979). We also include a discussion of the genus and a key to Australian species.